You are on page 1of 35

FUNCTIONS

Definition:
A relation is a set of ordered pairs of
numbers. The set of all first elements that occur in
a relation is the domain of the relation, and the set
of all second elements is the range of the relation.
Definition:
A function is a relation in which no two
ordered pairs have the same first element and
distinct second elements.
OPERATIONS OF
FUNCTIONS
The sum of f + g

(f + g) (x) = f(x) + g(x)

This just says that to find the sum of two


functions, add them together. You should simplify
by findings like terms.
Examples:
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

1. f(x) + g(x)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

2. f(x) + h(x) + g(x)


Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

3. f(3) + h(-1)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

4. f(2) + h(-4)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

5. f(5) + h(2) + g(3)


The difference of f – g
(f – g) (x) = f(x) – g(x)
To find the difference between two functions,
subtract the first from the second.
Caution: Make sure you distribute the – to
each term of the second function. You should
simplify by combining like terms.
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

1. f(x) – h(x)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

2. f(x) – h(x) – g(x)


Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

3. f(3) – h(1)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

4. f(2) – g(-4)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

5. f(5) – h(2) – g(3)


The product of f · g
(f · g) (x) = f(x) · g(x)
To find the product of two functions, put
parenthesis around them and multiply each term
from the first function to each term of the second
function.
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

1. f(x) · h(x)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

2. f(x) · h(x) · g(x)


Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

3. f(2) · h(3)
Given that:
f(x) = 2x2 + 3 ; g(x) = 4x + 1 ; h(x) = x2 + 3x – 5

4. f(1) · h(-2) · g(3)


The quotient of f / g
(f / g) (x) = f(x) / g(x)

To find the quotient of two functions, put the first


one over the second.
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

1. f(x) / h(x)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

2. f(x) / g(x)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

3. f(2) / g(6)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

4. g(3) / g(2)
Composition of
Functions
The Composition Function

(f ͦ g) (x) = f (g (x))
This is read “f composition g” and to find the
composition of f and g at a specific value of x, you
first apply g to x, and then you apply f to the result.
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

1. f(x) ͦ h(x)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

2. f(x) ͦ g(x)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x
3. f(x) ͦ g(x) ͦ h(x)
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x

4. f(g(3))
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x
5. f(h(-1))
Given that:
f(x) = 2x2 + 4x ; g(x) = x + 2 ; h(x) = 2x
6. f(g(h(-1)))
Activity 1: Apply the operations on functions
Given that:
f(x) = 3x + 3; g(x) = x2 – 2x + 1; h(x) = 2x2 – 2; j(x) = x2 – 1

1. f (x) + g(x) – j(x) 6. f (x) ∙ g (x) ∙ h (x)


2. g (2) – h (-3) – j (-5) 7. g (5) / h (2)
3. h (x) / f (x) 8. f (x) ͦ g (x)
4. g (x) / j (x) 9. h (j (1))
5. h (2) ∙ j (7) 10. g (f (j (5)))

You might also like